Mission to the World : Communicating the Gospel in the 21st Century: Essays in Honour of Knud Jørgensen - Strandenaes, Thor; Olsen, Rolv; Harbakk, Ernst; Engelsviken, Tormod (Book collections on Project MUSE., 2008)
The title of the festschrift, Mission to the World: Communicating the Gospel in the 21st Century: Essays in Honour of Knud Jorgensen , indicates a program that reflects the various main areas of Knud Jorgensen 's commitment to mission. At the same time, it focuses on the main frontier of mission, the world; the content of mission, the gospel; the fact that the gospel has to be communicated; and the context of contemporary mission, the 21st century.Knud Jorgensen is firmly planted in the church, with a strong evangelical, ecumenical, charismatic, and Lutheran spirituality expressed in clear theological convictions. He is a man with a great vision for the future of the church in mission in a global perspective--a vision that he pursues with strength, wisdom, and integrity. By using his gifts he has functioned as a theological teacher, an inspiring preacher, and a thoughtful advisor in many contexts and to a variety of people. His leadership qualities have brought him into leading positions in several organizations on the local, national, and global levels and have made him able to lead others to achieve high common goals. He is a man with an unusual energy and effectiveness, who is able to carry out his plans and visions in practice. This festschrift is a tribute to him from his many friends and colleagues around the world, and at the same time, a contribution to critical reflection on a wide variety of contemporary missiological issues.